Analisis Data Observasi Sebagai Dasar Refleksi Dalam Penelitian Tindakan Kelas:Kajian Literatur - Siti Aisyah Putri Andiyani; Maysaroh; Aprilia Yuliantika; Dewi Indah Wulandari; Imron Fauzi (Yayasan Al-Afif, 2026)
This study aims to analyze the role of observational data analysis as the basis for reflection in classroom action research thourgh a systematic literature review (SLR). The study examines how observational data contribute to reflective practice, intructional improvement, and teacher professionalism. This research employed a qualitative approach using the SLR methos by analyzing national and international journal articles published within the last five years. The review process included literature identification, selection, evaluation, data extraction, and thematic synthesis. The findings indicate that observation serves as the primary empirical data source in classroom action research because it provides factual information about classroom activities, student participation, and intructional affectiveness. observational data analysis supports objective and evidence based reflection, enabling teachers to evaluate learning strategies and improve subsequent instructional actions. The novelty of this study lies in its integrative analysis of observation and reflection as a unified mechanisin that contributes to sustainable intructional improvement and teacher professional development.